Patients’ Perspective on Doctor’s Attire - Shrestha, Abha; Shrestha, Bikash; Amatya, Ram Chaya; Chawla, CD (Nepalese Journal of ENT Head and Neck Surgery, 2014)
DOI: http://dx.doi.org/10.3126/njenthns.v3i2.10161 Nepalese Journal of Head and Neck Surgery Vol.3(2) 2012: 23-25